Modeling the angular effect of MODIS LST in urban areas: A case study of Toulouse, France - Wang, Dandan; Chen, Yunhao; Hu, Leiqiu; Voogt, James A.; Gastellu-Etchegorry, Jean-Philippe; Krayenhoff, E. Scott (Remote sensing of environment, 2021)
Satellite observation of land surface temperature (LST) is an important tool for monitoring urban thermal environments but is prone to significant angular effects over non-isothermal pixels characterized by the substantial three-dimensional (3D) structure of urban areas. However, accurately characterizing the urban thermal anisotropy at the satellite pixel scale is still challenging. In this paper, comparing the simultaneous airborne observations and the temporal-aggregated signal from MODIS LST, we further investigate the seasonal and diurnal patterns of thermal anisotropy in urban areas with various simulation scenarios. The anisotropy was defined as the difference between off-nadir and nadir temperatures. First, a realistic morphological representation of urban surfaces as well as urban component temperatures measured by infrared thermometers (IRTs) were input into the discrete anisotropic radiative transfer (DART) model to simulate MODIS-scale anisotropy for Toulouse, France in summer. Extending this ‘IRT-DART’ method to other seasons was restricted because the IRTs' radiative source areas are affected by shadows when the sun elevation is low, meaning that measured sunlit temperatures are not reliably available. An energy balance model, TUF3D, and a sensor view model, SUM, for simplified urban geometry were coupled to replace ‘IRT-DART’ in winter. The cross-comparison shows that ‘TUF-SUM’ can simulate MODIS-scale anisotropy if urban structure and materials are relatively homogeneous, which provides a basis for assessing anisotropy when IRT sunlit temperatures are unavailable. The MODIS anisotropy is subject to a strong diurnal yet a discernable seasonal variation. For example, for a mid-latitude city, the anisotropy over all MODIS view angles reaches up to 6.6 K for Terra-Day (around 11:00 local time) and 4.9 K for Aqua-Day (around 13:00) in summer, and 6.1 K for Terra-Day and 4.0 K for Aqua-Day in winter. Nocturnal anisotropy is weak with values less than 0.2 K. The modeling methods can be used to quantify anisotropy of satellite LST in a broad range of urban environments and facilitate the use of multi-angular MODIS LST for a better assessment of urban thermal environments in the future. •MODIS-scale thermal anisotropy is simulated for a mid-latitude city.•Anisotropy from DART upscaled observed temperatures replicates airborne patterns.•The TUF-SUM combination provides high-quality seasonal anisotropy estimates.•Anisotropy distribution shape varies seasonally.•Strong daytime anisotropy for both summer and winter is found, reaching up to 6.6 K.